PENERAPAN PENILAIAN MANAJEMEN MUTU DI INSTITUT AGAMA ISLAM NEGERI PALANGKA RAYA - Fahmi Fahmi; Fimeir Liadi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
ABSTRACTThe results of the discussion in the application of Quality Management at the State Islamic Institute of Palangka Raya, consist of three supporting elements, namely: first, the structure, with regard to communication, authority and workflow. The structure is often also called the chain of command, and is depicted graphically using an organizational chart; second, culture, is a pattern of beliefs, expectations, and values that apply among members of the organization; and third, resources, which include the managerial skills, abilities, and talents of each member of the organization. To assess the scope of this can be done by using the ten characteristics contained in Quality Management, namely: 1) focus on customers; 2) obsession with quality; 3) scientific approach; 4) long-term commitment; 5) team work (teamwork); 6) continuous system improvement; 7) education and training; 8) restrained freedom; 9) unity of purpose; and 10) employee engagement and empowerment. For the highly competitive State Islamic Institute of Palangka Raya, a commitment to quality will give satisfaction to students and lecturers as well as the general public which is non-negotiable. And if this is well received, the Palangka Raya State Islamic Institute of Religion will certainly change its status to a University in 2023 or before 2025.keywords: Application, assessment, quality management of the Palangka Raya State Islamic Institute ABSTRAKHasil pembahasan dalam penerapan Manajemen Mutu di Institut Agama Islam Negeri Palangka Raya, terdiri atas tiga unsur pendukung, yaitu: pertama, struktur (structure), berkenaan dengan komunikasi, wewenang dan alur kerja. Struktur sering juga disebut rantai komando, dan digambarkan secara grafis menggunakan bagan organisasi; kedua, budaya (culture), merupakan pola keyakinan, harapan, dan nilai yang berlaku di antara anggota organisasi; dan ketiga, sumber daya, yang meliputi keahlian, kemampuan, dan bakat manajerial seseorang dari setiap anggota organisasi. Untuk menilai ruang lingkup tersebut dapat dilakukan dengan menggunakan sepuluh karakteristik yang terdapat dalam Manajemen Mutu, yaitu: 1) fokus pada pelanggan; 2) obsesi dengan kualitas; 3) pendekatan ilmiah; 4) komitmen jangka panjang; 5) kerja tim (teamwork); 6) perbaikan sistem yang berkesinambungan; 7) pendidikan dan pelatihan; 8) kebebasan yang terkendali; 9) kesatuan tujuan; dan 10) pelibatan dan pemberdayaan karyawan. Bagi Institut Agama Islam Negeri Palangka Raya yang sangat kompetitif ini, komitmen terhadap mutu akan memberikan kepuasan kepada mahasiswa dan dosen serta masyarakat umumnya yang tidak dapat ditawar lagi. Dan apabila ini dapat diterima dengan baik maka Institut Agama Islam Negeri Palangka Raya ini dapat dipastikan akan berubah statusnya menjadi Universitas di tahun 2023 atau sebelum tahun 2025.kata kunci: Penerapan, penilaian, manajemen Mutu Institut Agama Islam Negeri Palangka Raya